Influences of functionalized nanoclays on morphology and mechanical properties of polyvinyl alcohol based composites by twin-screw extruder - Rajeswari, B.; Malarvizhi, N.; Elumalai, Deenadayalan; Jaisankar, Sellamuthu N. (Polymer-Plastics Technology and Engineering, 2017)
Polyvinyl alcohol (PVA) based nanocomposites filled with different weight percentage of functionalized nanoclays were prepared by melt processing with a twin-screw extruder. The effective incorporation of amine modified bentonite nanoclays (AMB) in the PVA matrix leads to increase in thermal stability, stress-strain properties. The effect of addition of functionalized nanoclays in PVA matrix exhibits intercalated nanocomposite structure. The thermal decomposition (Td) temperature of the composites increases up to 30 °C, than pristine PVA. The morphology influences were studied by TEM. These clay nanocomposite films could be useful for wound dressing material and for enhancing the moisture absorbance properties.